Brominated and organophosphorus flame retardants in South African indoor dust and cat hair. (October 2019) - Brits, Martin; Brandsma, Sicco H.; Rohwer, Egmont R.; De Vos, Jayne; Weiss, Jana M.; de Boer, Jacob
Abstract: Flame retardants (FRs), such as brominated flame retardants (BFRs) and organophosphorus flame retardants (OPFRs), are diverse groups of compounds used in various products related to the indoor environment. In this study concentrations of eight polybrominated diphenyl ethers (PBDEs), two alternative BFRs and ten OPFRs were determined in indoor dust (n = 20) and pet cat hair (n = 11) from South Africa. The OPFRs were the major FRs, contributing to more than 97% of the total FR concentration. The median Ʃ10 OPFRs concentrations were 44, 800 ng/g in freshly collected dust (F-dust), 19, 800 ng/g in the dust collected from vacuum cleaner bags (V-dust), and 865 ng/g in cat hair (C-hair). Tris(1-chloro-2-propyl) phosphate (TCIPP) was the dominant OPFR in the dust samples with median concentrations of 7, 010 ng/g in F-dust and 3, 590 ng/g in V-dust. Tris(2-butoxyethyl) phosphate (TBOEP) was the dominant OPFR in C-hair, with a median concentration of 387 ng/g. The concentrations of Ʃ8 PBDEs were higher in F-dust than in V-dust. BDE209 was the dominant BFR in all three matrices. Bis(2-ethylhexyl)-3, 4, 5, 6-tetrabromo-phthalate (BEH-TEBP) and 2-ethylhexyl-2, 3, 4, 5- tetrabromobenzoate (EH-TBB) showed notable contributions to the BFR profile in cat hair. A worst-case dust exposure estimation was performed for all analytes. The estimated TCIPP daily intake through dust ingestion was up to 1, 240 ng/kg bw for toddlers. The results indicate that OPFRs are ubiquitous in South African indoor environment. Indoor dust is a major source of human exposure to environmental contaminants. This can for example occur through hand-to-mouth contact of toddlers, and is an important route of exposure to currently used FRs accumulated on dust particles. The presence of FRs, in particular high concentrations of OPFRs, suggests that children and indoor pet cats may have greater exposure to FRs than adults. Graphical abstract: Image 1 Highlights: First report on chloroalkyl, aryl and alkyl OPFRs in the South African indoor environment. First results of OPFRs in cat hair as a non-invasive sampler for human exposure, aimed at toddlers. OPFRs are the major FRs and contribute for more than 97% to the total FR load. TCIPP is the major OPFR in indoor dust and TBOEP the major OPFR in cat hair. BEH-TEBP and EH-TBB showed notable contributions to the BFR profile in cat hair. Abstract : The quantitative analysis of brominated and organophosphorus flame retardants in indoor dust and cat hair shows higher concentrations of organophosphorus flame retardants; chloroalkyl phosphates were prominent in dust and alkyl phosphates in cat hair.